The development of a gamification-based evaluation tool for the creative projects and entrepreneurship subject in grade XI - Yunanda Ahmad; Hamsu Abdul Gani; Abdul Hakim (Journal of Research in Instructional, 2026)
Technology in evaluation can improve the efficiency, accuracy, and quality of learning assessments.  This study aims to develop a valid, practical, and effective gamification-based learning evaluation tool for the Creative Products and Entrepreneurship subject. The research employed a Research and Development (R&D) approach using the ADDIE development model. The study was conducted at UPT SMK Negeri 2 Bone, with research subjects including Grade XI DKV students, one Creative Projects and Entrepreneurship teacher, and two expert validators, namely a subject-matter expert and a media expert. Data were analyzed using descriptive qualitative and quantitative techniques. The results indicate that both teachers and students require evaluation tools that are efficient, interactive, and digitally based. The gamification-based evaluation tool was developed in accordance with the learning outcomes and instructional objectives using Canva and ClassPoint applications. Validation results show that the evaluation tool falls into the valid category. The practicality of the evaluation tool is classified as very practical based on teacher and student response questionnaires. The effectiveness of the evaluation tool is demonstrated by classical learning mastery that exceeds the predetermined mastery threshold through post-test results. Therefore, the gamification-based evaluation tool is considered feasible and effective for use as a learning evaluation tool in Grade XI classrooms.